The 2nd International Electronic Conference on Nutrients 2022
DOI: 10.3390/iecn2022-12376
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Features and Biological Effects of Astaxanthin Extracted from Haematococcus pluvialis Flotow: Focus on Gastrointestinal System

Abstract: This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https:// creativecommons.org/licenses/by/ 4.0/).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…A study conducted on hypertensive mice treated with natural astaxanthin revealed its ability to prevent atherosclerosis, significantly reduce blood pressure, and delay the occurrence of stroke. These findings indicate that astaxanthin holds the potential in safeguarding against hypertension and stroke [1]. Furthermore, in patients at risk of cardiovascular disease, astaxanthin has shown promise in the treatment of myocardial injuries, thrombolysis, and other heart-related conditions.…”
Section: Cardiovascular Activitymentioning
confidence: 88%
See 3 more Smart Citations
“…A study conducted on hypertensive mice treated with natural astaxanthin revealed its ability to prevent atherosclerosis, significantly reduce blood pressure, and delay the occurrence of stroke. These findings indicate that astaxanthin holds the potential in safeguarding against hypertension and stroke [1]. Furthermore, in patients at risk of cardiovascular disease, astaxanthin has shown promise in the treatment of myocardial injuries, thrombolysis, and other heart-related conditions.…”
Section: Cardiovascular Activitymentioning
confidence: 88%
“…Both in vitro and in vivo studies have demonstrated that astaxanthin exhibits superior anti-inflammatory effects compared to common medications [16]. Consequently, natural anti-inflammatory substances such as astaxanthin are extensively utilized for the prevention and management of inflammatory conditions due to their ability to inhibit the production of nitric oxide (NO), prostaglandin E2 (PGE2), and pro-inflammatory cytokines [1,47]. Furthermore, research has shown that astaxanthin derived from the microalga H. pluvialis is effective in alleviating symptoms of ulcers caused by Helicobacter pylori and reducing gastric inflammation [48].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, the esterified biological form of ASTX displays higher bioavailability compared with synthetic ester-free derivatives [70][71][72][73], suggesting the need to improve its production from natural sources. However, a major limitation to the clinical use of ASTX lies in its low solubility in gastrointestinal fluids [74], requiring encapsulation in polysaccharide, lipid, and protein nanoparticles to enhance its delivery and release [75][76][77][78][79][80].…”
Section: Astaxanthin: the Red Gold Of Algaementioning
confidence: 99%